Synthesis of High‐Performance Monolayer Molybdenum Disulfide at Low Temperature. Issue 6 (19th April 2021) - Park, Ji‐Hoon; Lu, Ang‐Yu; Shen, Pin‐Chun; Shin, Bong Gyu; Wang, Haozhe; Mao, Nannan; Xu, Renjing; Jung, Soon Jung; Ham, Donhee; Kern, Klaus; Han, Yimo; Kong, Jing
Abstract: The large‐area synthesis of high‐quality MoS2 plays an important role in realizing industrial applications of optoelectronics, nanoelectronics, and flexible devices. However, current techniques for chemical vapor deposition (CVD)‐grown MoS2 require a high synthetic temperature and a transfer process, which limits its utilization in device fabrications. Here, the direct synthesis of high‐quality monolayer MoS2 with the domain size up to 120 µm by metal‐organic CVD (MOCVD) at a temperature of 320 °C is reported. Owing to the low‐substrate temperature, the MOCVD‐grown MoS2 exhibits low impurity doping and nearly unstrained properties on the growth substrate, demonstrating enhanced electronic performance with high electron mobility of 68.3 cm 2 V −1 s −1 at room temperature. In addition, by tuning the precursor ratio, a better understanding of the MoS2 growth process via a geometric model of the MoS2 flake shape, is developed, which can provide further guidance for the synthesis of 2D materials. Abstract : The synthesis of high‐quality monolayer MoS2 is important for the fabrication of high‐performance next‐generation devices. Monolayer MoS2 is grown with a domain size up to 120 µm by the MOCVD at low temperature and the growth mechanism is understood via modeling. Also, a MoS2 transistor shows enhanced performance with high electron mobility of 68.3 cm 2 V −1 s −1 .